Distress Reduction for Palliative Care Patients and Families With 5-Minute Mindful Breathing: A Pilot Study. (July 2016) - Beng, Tan Seng; Ahmad, Fazlina; Loong, Lam Chee; Chin, Loh Ee; Zainal, Nor Zuraida; Guan, Ng Chong; Ann, Yee Hway; Li, Lee Mei; Meng, Christopher Boey Chiong
A pilot study was conducted to evaluate the efficacy of 5-minute mindful breathing in distress reduction. Twenty palliative care patients and family caregivers with a distress score ≥4 measured by the Distress Thermometer were recruited and randomly assigned to mindful breathing or "listening" (being listened to). Median distress reductions after 5 minutes were 2.5 for the mindful breathing group and 1.0 for the listening group. A significantly larger reduction in the distress score was observed in the mindful breathing group (Mann-Whitney U test: U = 8.0, n1 = n2 = 10, mean rank1 = 6.30, mean rank2 = 14.70, z = −3.208, P = .001). The 5-minute mindful breathing could be useful in distress reduction in palliative care.